2009
DOI: 10.1007/s10209-009-0153-4
|View full text |Cite
|
Sign up to set email alerts
|

A web accessibility assessment on the Texas public school system

Abstract: As the World Wide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Despite these overall advances, studies of different educational and course websites have nevertheless detected accessibility-limiting barriers for certain users [1] [2]. Moreover, accessibility-related problems have also been identified in numerous LCMSs currently used (see sub-section Evaluations of accessibility in educational authoring tools).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these overall advances, studies of different educational and course websites have nevertheless detected accessibility-limiting barriers for certain users [1] [2]. Moreover, accessibility-related problems have also been identified in numerous LCMSs currently used (see sub-section Evaluations of accessibility in educational authoring tools).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, difficulties have been detected in certain LCMSs where authors' prior programming skills are assumed or required [1]. Visually-impaired users, in particular, are 1 constantly confronted with barriers when surfing the Internet that often take the form of (1) identicallynamed, redundant or confusingly similar links [4], (2) images used without accompanying, alternative text and (3) colors or other visual, non-linguistic elements -used to convey information [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 25 papers selected, 14 papers detail disability laws that promote improved quality of life for people with disabilities. The disability laws used in the papers are listed below (see full information in Table 8, Appendix A): • Paper [35] • Paper [57], [58] Americans with Disabilities Act (ADA).…”
Section: ) Rq3 What Is the Frequency Of Publication Of Web Accessibmentioning
confidence: 99%
“…Although it is an audio device, these files are represented by an image of an audio resource and this should be described to visually disabled people. One study evaluated the accessibility of school websites in Texas and found that most accessibility errors were related to the lack of description of non-textual elements (May & Zhu, 2010). Similarly, a study that evaluated public websites in Greece found that the predominant error was the lack of description of these elements (Basdekis, Klironomos, Metaxas, & Stephanidis, 2010).…”
Section: Accessibility Assessment Of Html Pagesmentioning
confidence: 99%